Coffee Clinic Marketing Communication Strategy Through Instagram Live Social Media Storytelling - Nabila Cahyani Putri; Maylanny Christin (PT Mattawang Mediatama Solution, 2024)
The use of storytelling is of course related to current technological developments, almost most social media offer streaming options that allow interaction with other users. One streaming option that is often used for storytelling by the public is the live streaming feature. Storytelling itself is used as a marketing communication tool as a differentiation effort to attract consumer attention. Apart from increasingly rapid technology, the development of the business world has increased quite significantly, this includes the business industry that is currently developing, namely the coffee shop phenomenon. In the business world, of course there are different marketing communication strategies according to their target consumers, plus this has a very important role in forming consumer understanding and awareness. The aim of this research is to identify the marketing communication strategy carried out by the Coffee Clinic through Instagram live social media storytelling and what message and media strategies are used in marketing communications through Instagram Live social media storytelling at the Coffee Clinic. This research uses a qualitative method where information is collected through interviews, observation and documentation with selected informants. The data analysis technique is carried out by reducing, then presenting the data and drawing conclusions from the results obtained. The results of this research explain the marketing communication strategy carried out by the Coffee Clinic through Instagram Live storytelling, of course linked to the marketing communication strategy theory by (Machfoedz, 2010) which includes message and media strategies